Investigation Unit II/Economics of Nganjuk Police Satintelkam into the 3 Kilogram LPG Scarcity - Satyabharda, Ansyah Bhakti (Indonesian Journal of Police Studies, 2024)
This Final Project article analyzes the investigation efforts of the Unit II Satintelkam of Nganjuk Police Resort in the case of the 3-Kilogram LPG Difficulty that occurred in June 2023. The approach used is the Meho-Tibbo Theory of Information Discovery and SOAR Analysis, focusing on the factors influencing the investigation. The research method employed is qualitative with a case study design, and data collection was done through interviews, observations, and documentary studies. The study found that there were difficulties for the community in obtaining 3-Kilogram LPG during that month, which caught the attention of the Nganjuk Police Resort. Unit II Satintelkam of Nganjuk Police Resort conducted the investigation using various techniques with stakeholders. However, the analysis results indicate that the investigation was not entirely in accordance with Perkabaintelkam regulations and was influenced by factors identified in the SOAR Analysis. This research contributes to understanding the investigative efforts in the 3 Kilogram LPG scarcity case and the factors influencing Satintelkam Polres Nganjuk’s investigations. Recommendations are provided for improvements in police investigation implementation in the future.